2006
DOI: 10.1007/bf03344100
|View full text |Cite
|
Sign up to set email alerts
|

Changes in calcium, 25(OH) vitamin D3 and other biochemical factors during pregnancy

Abstract: 60% of women in the first trimester, 48% in the second and 47% in the third trimester had either severe or moderate vitamin D deficiency. It is recommended that the importance of calcium supplements with vitamin D in pregnant women be stressed for these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 20 publications
2
35
1
1
Order By: Relevance
“…A study in Iran [29], showed that 19 % of pregnant women had hypocalcemia (i.e. serum calcium level below 8.5 mg/dl).…”
Section: Discussionmentioning
confidence: 99%
“…A study in Iran [29], showed that 19 % of pregnant women had hypocalcemia (i.e. serum calcium level below 8.5 mg/dl).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Saudi Arabia, Kuwait, United Arab Emirates, and Iran reveal that 10-60% of mothers and 40-80% of their neonates had undetectable low vitamin D levels (0-25 nmol/L) at delivery [112][113][114][115]. Neonatal outcomes were not detailed in most studies.…”
Section: Middle East and Africamentioning
confidence: 99%
“…The Middle East, the land of every day sun, is by no means an exception. Studies conducted in Iran and neighboring countries clearly demonstrate severe vitamin D deficiency in different age groups, especially in women, most probably because of the type of clothing and deficient oral intake of vitamin D, which is 50-110 U per day (Sedrani et al, 1983;Alagol et al, 2000;Hashemipour et al, 2004;Mirsaeid Ghazi et al, 2004;Ainy et al, 2006;Dahifar et al, 2007;Baroncelli et al, 2008). Mean daily intake of calcium (Ca) is 580-600 mg (Du et al, 2001;El-Hajj Fuleihan et al, 2001), hence the people in the region have mixed Ca and vitamin D deficiency.…”
Section: Introductionmentioning
confidence: 99%